Time, Salary, and Incentive Payoffs in Labor Contracts - Fama, Eugene F. (Journal of Labor Economics, 1991)
Time (hourly payoffs) and salary (the payoff does not vary with hours) account for the bulk of the payoffs on labor contracts. This article argues that the choice between time and salary centers on the presence (time) or absence (salary) of information about flows of effort or output per unit time. Without information about the flow of hourly effort or output, payoffs for time give the worker an incentive to supply hours without effort. Time can then become uninformative about output. In this situation, if the contract includes a fixed payoff, it is likely to be a salary rather than a payoff for time.